A multi-faceted evaluation of the impact on students of an Australian university-wide academic language development program. Issue 60 (November 2022) - Goldsmith, Rosalie; Havery, Caroline; Edwards, Emily; James, Neil; Murphy, Aurora; Mort, Pamela; Nixon, Deborah; O'Donoghue, Gemma; Yang, Jin Sug; Yeo, Joseph
Abstract: In response to the ongoing need to support all students' academic language development throughout their university studies, the academic language and learning team at an Australian university has established the Academic Language Development (ALD) program. This program screens all commencing students at the university and offers an innovative whole-of-institution approach to discipline-specific language development. The purpose of this paper is to report on a large-scale, long-term and multi-faceted evaluation of the ALD program, considering the impact of attending compulsory language development tutorials on 3922 students, the majority of whom were L2 users of English. Surveys have been carried out and data collected on academic language development, academic outcomes, student perceptions of their confidence, and other gains from attending the tutorials. A particular focus of this analysis is on the affective aspects of language development. In addition to developing academic language proficiency, the findings show that students benefited in multiple ways from the ALD program. Key themes emerged from the data around confidence, agency, and social connections, as well as a greater ability to navigate the university landscape. This paper offers an innovative approach to the evaluation of language programs that will be relevant to those teaching and researching linguistically diverse cohorts across faculties in higher education.